Ideological Representations of Hate Speech Comments against Women on Indonesian TikTok: A Critical Discourse Analysis - Mimo Lalito Erisyerico; Ni Luh Putu Sri Adnyani; I Made Suta Paramarta (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
TikTok is one of the most popular social media platforms in Indonesia, enabling users to share short videos and engage through comments, likes, and shares. Comments on these videos frequently reflect social judgments and moral evaluations, particularly toward female public figures. The present study investigates the ideological messages represented in hate speech comments against women on TikTok. The data were taken from four Ayu Ting Ting (henceforth, ATT) concert videos uploaded in August 2025, selected for their high engagement and numerous negative comments, in which ATT is a famous Indonesian dangdut singer whose popularity often attracts strong public attention and online reactions. A total of 3,619 comments were analyzed using van Dijk’s Socio-Cognitive Approach (SCA) to Critical Discourse Analysis (CDA) to reveal the relationship among textual content, social cognition, and social context. The analysis found that five dominant ideological themes are expressed through the hate speech comments, namely religiosity, racism or ethnocentrism, gender or sexism, social class or economic inequality, and nationalism or xenophobia. It was also shown that polite, humorous, or sarcastic forms frequently contained hate speech, while moral judgment, social control, and discriminatory meanings were conveyed implicitly. The current study illustrates how social norms, moral expectations, and hierarchical power relations are reproduced in online discourse, showing the ways women are socially regulated and marginalized within digital spaces; therefore, this study contributes to a deeper understanding of implicit hate speech and the reinforcement of social ideologies in Indonesia.